Vru (Sub0144) controls expression of proven and putative virulence determinants and alters the ability of Streptococcus uberis to cause disease in dairy cattle - Egan, Sharon A.; Ward, Philip N.; Watson, Michael; Field, Terence R.; Leigh, James A. (Society for General Microbiology, 2012)
The regulation and control of gene expression in response to differing environmental stimuli is crucial for successful pathogen adaptation and persistence. The regulatory gene vru of Streptococcus uberis encodes a stand-alone response regulator with similarity to the Mga of group A Streptococcus. Mga controls expression of a number of important virulence determinants. Experimental intramammary challenge of dairy cattle with a mutant of S. uberis carrying an inactivating lesion in vru showed reduced ability to colonize the mammary gland and an inability to induce clinical signs of mastitis compared with the wild-type strain. Analysis of transcriptional differences of gene expression in the mutant, determined by microarray analysis, identified a number of coding sequences with altered expression in the absence of Vru. These consisted of known and putative virulence determinants, including Lbp (Sub0145), SclB (Sub1095), PauA (Sub1785) and hasA (Sub1696).